Fairy tail. 38 - Mashima, Hiro, 1977- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2014)
"In the final matches of the Grand Magic Games, a wounded Erza struggles against a sadistic Minerva who can twist space itself, Gajeel sinks into the shadows against a powered-up Rogue, and Laxus faces down impossible odds against Jura, the world's fifth-strongest wizard. But as the Games end, the kingdom prepares for a day Natsu never thought he'd see: the return of the dragons." --Back cover.